(untitled) (Proceedings of the World Conference on Children and Youth, 2021)
Children who are sexually abused are likely to encounter discrimination, feel blameworthy, and a lack of support from the very people who should support them. Questions asked of the victim, such as “why were you raped," are the norm, though it is the perpetrator who should be asked why he raped. More importantly, poverty in families is both a cause and an effect of child sexual abuse. This paper employs doctrinal research methodology to examine the attitudes to, and cultural perspectives of, child sexual abuse and the relevance of poverty-reduction policies in addressing child sexual abuse. It is argued that there is a link between cultural ideologies and poverty when it comes to child sexual abuse in Tanzania. There, for example, children are abused on the grounds of superstition and the belief that sexual intercourse by an adult with a child will make the perpetrator rich. Furthermore, because of poverty, families are reluctant to report sexual abuse committed within the confines of the family, especially when the perpetrator is a breadwinner, or when there is “compensation”. This paper concludes that, despite the fact that Tanzania has taken various measures to address child sexual abuse, cultural ideologies should be addressed hand in hand with comprehensive policies on poverty reduction when addressing child sexual abuse.